SISTEM MONITORING DISERTASI PROGRAM DOKTOR ILMU KOMPUTER UNIVERSITAS GADJAH MADA - , FAJAR BARRUN NUGROHO, Sigit Priyanta, S.Si, M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Along with the increasing of the number of Doctoral programâs students of Computer Science, inUniversity of Gadjah Mada, the quality of service for the Doctoral Program needs to be improved. In conducting dissertation research, students need for guidance from a Team of Promoter. Now, the guidance is still has to be done manually, the students are required to meet with the Promoter, but it not efficient because something might happen and make that students and the Promoter cannot meet each other.So,a system that can help the guidance process for the studentsis needed to be made. Based on the problems, a system that is able to monitor the development of the dissertation research will be built, so that students can be guided by the promoter without limitation of time. This information system is built using the PHP Hypertext Preprocessor (PHP) programming language with CodeIgniter framework. In the manufacture of user interface's system, using Cascading Style Sheets (CSS) Bootstrap order processing easier. The system uses MySQL for its database management. The dissertation monitoring system for Doctoral Program Computer Science, University ofGadjah Mada can be used to monitorprogress of the studentâs dissertationâs research, and can be used by administrators to manage the student'sgrade subjects and determine reviewers in the three months development of dissertation.